Effectiveness of robot-based pivotal response treatment for children with autism - A systematic review - Nasirabadi, Minhajzafar; Mehrukh, Arman; Ali, Mazher; Ali, Khan Mohammed Zeeshan; Ahmed, Arifuddin (Telangana Journal of Psychiatry, 2024)
Introduction: Autism spectrum disorder has shown rising incidence and increasing cost of healthcare over the past few years. Robot-based interventions are an attempt to overcome the shortage of trained therapists for children with autism. Materials and Methods: This systematic review aims at examining the efficacy of robot-based pivotal response treatment (PRT) in the treatment of children with autism. It aimed to answer the following questions - which robots are used to administer PRT, which aspects of PRT can be targeted by robots, and what factors influence outcome in robot-based PRT. Peer-reviewed clinical trials and randomized controlled trials from the last 10 years were included. Results: The social robot NAO was the most commonly used intervention. Joint attention was the most commonly studied aspect. Outcome depended on the design of the intervention and the baseline functioning of the child with autism. Conclusion: The review found that there are modest gains in robot-based PRT and that it can be beneficial in providing therapy to children with autism.